Online Alumni Information System Satisfies Alumni in an Educational Institution in Cebu City, Philippines - Alegado, Laila M. (JPAIR Institutional Research, 2015)
The internet is a powerful tool for connectivity. It has become the avenue for most people to exchange information, knowledge, and apparently, almost everyone is present on the web. The Online Alumni Information System aimed to evaluate the status of the existing alumni information system in the aspect of accessibility, reliability and timeliness. It also identified the problems encountered in the current alumni information system, determine the features of good online alumni information system, and design a prototype of online alumni information system. The study used the descriptive method of research using the researcher-made questionnaire to gather data. There were 116 respondents in the study using purposive sampling technique. To obtain the relevant data, the alumni provide their answers to the researcher-made questionnaire. The results revealed that the respondents were able to acquire accurate documents or alumni information from the school after graduation, and they were satisfied with those obtained documents. The common problems encountered include the absence of the programs/ activities organized by the alumni, no communication with the graduates, and outdated profiles of the graduates. The study concludes that an Online Alumni Information System should be designed and developed to provide easy access to information to all stakeholders.
Keywords: Online alumni information system; alumni; descriptive design; Philippines